PENGARUH BREASTCARE DAN AROMATERAPI LAVENDER TERHADAP PRODUKSI ASI IBU MENYUSUI DI TPMB WILAYAH KECAMATAN SENDURO KABUPATEN LUMAJANG - Yunita Ashadi Putri, Intan (NHM PRESS, 2024)
Breast care is one of the important factors that can influence breast milk production for breastfeeding mothers. Using Lavender Aromatherapy essential oil can help mothers relax and feel comfortable so that it is hoped that breast milk production can increase. This research aims to find out whether the breastcare method and lavender aromatherapy have an effect on the smooth production of breast milk by breastfeeding mothers. This research used a quasi-experimental design with a posttest only only control group design was conducted at the TPMB in the Senduro District area from January 1 to April 25 2024. Breastfeeding mothers in the TPMB in the Senduro District area during that time period were used as the population. Purposive sampling obtained 32 breastfeeding mothers divided into 2 groups. The control group provided breastcare with 16 respondents, 9 of whom had smooth breastfeeding and 7 with non-fluent breastfeeding. The experimental group consisted of 16 respondents who provided breastcare and lavender aromatherapy where all respondents had good breast milk. Mann Whitney test analysis obtained a p-value of 0.003 < 0.05. So that providing breastcare and lavender aromatherapy has an effect on breast milk production for breastfeeding mothers in TPMB Senduro District, Lumajang Regency